Tipping points in freshwater ecosystems: an evidence map - Hernández Martínez de la Riva, Ana; Harper, Meagan; Rytwinski, Trina; Sahdra, Angeli; Taylor, Jessica J.; Bard, Brittany; Bennett, Joseph R.; Burton, Declan; Creed, Irena F.; Haniford, Laura S. E.; Hanna, Dalal E.; Harmsen, Evaline J.; et al. (Frontiers in Freshwater Science, 2023)
Freshwater ecosystems face numerous threats, including habitat alteration, invasive species, pollution, over extraction of resources, fragmentation, and climate change. When these threats intensify and/or combine with each other, their impacts can shift the ecosystem past a tipping point, producing a major and potentially irreversible shift in state, called a regime shift. We generated an evidence map to assess the current state of knowledge on tipping points in freshwater ecosystems. Our evidence mapping exercise revealed large knowledge gaps. Specifically, there are relatively few studies that explore the effects of tipping points in relation to (1) lotic systems (i.e., rivers, streams), (2) amphibians, mammals, or reptiles, and (3) the interactive impacts of multiple threats. In addition, most studies tended to have short study durations (<1 year), and few studies explored the reversibility of an ecosystem change after a tipping point was crossed. Concentrating future research on these gaps to improve understanding of tipping points in freshwater ecosystems in a holistic manner is important to help develop tools to forecast (and thus mitigate) the emergence and effects of tipping points, as well as to guide restoration actions.